Isolation of Mycobacterium avium ssp. paratuberculosis and other non-tuberculous mycobacteria from head lymph nodes of wild ruminants and badgers in Switzerland - Lienhard, Julia; Friedel, Ute; Paganini, Claudio; Hilbe, Monika; Scherrer, Simone; Schmitt, Sarah (Frontiers in Veterinary Science, 2024)
Introduction The family Mycobacteriaceae contains over 188 species, most of which are saprophytic non-tuberculous mycobacteria (NTM). In wildlife, a variety of different NTM can be found, with different reports about their pathogenic potential. A pathogenic member of NTM is Mycobacterium avium ssp. paratuberculosis (MAP), which can infect farmed and wild ruminants. It causes paratuberculosis which is an economically important chronic disease. Infected farm animals are considered to be the source of infection in wild animals. Wildlife, on the other hand, is thought to be a reservoir for certain members of the Mycobacterium tuberculosis complex (MTBC), such as M. caprae, which causes tuberculosis in cattle and red deer. Methods Switzerland implemented a surveillance program for tuberculosis in wild animals in 2014. Here, we describe the results from the mycobacterial culture of lymph node samples collected from red deer, roe deer, chamois, ibex, and badgers collected within this surveillance program from 2020 to 2022. Overall, samples from 548 animals were checked macroscopically for tuberculosis-like lesions. Results In total, 88 animals (16.1%), which either had lesions in their lymph nodes or were male and aged older than 5 years, were investigated using mycobacterial culture. In total, 25 animals (28.4%) were positive for NTM, while no MTBC was detected. The most often identified NTM was M. vaccae, followed by M. avium. Most animals positive for NTM did not show any macroscopic lesions. Furthermore, MAP was isolated from the head lymph nodes of two male red deer. Neither of the two MAP-positive animals had any macroscopic lesions in their head lymph nodes or any other signs of disease. Discussion The shooting sites of the two MAP-positive animals were located in Alpine pastures used for grazing of cattle during summer, which confirms that species transmission can occur when contaminated pastures are used by different species. In agreement with other studies, the occurrence of MAP in red deer was quite low. However, so far, MAP was mostly isolated from feces and intestinal lymph nodes of wild animals. This is the first detection of MAP in the head lymph nodes of red deer in Switzerland.